THE EFFECT OF WORK COMMUNICATION, WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. ATREO AMNYNTAS MUBARAK BATAM - Sitinjak, Diskon; Sumardin, Sumardin; Suyono, Suyono; Sabri, Sabri (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyse the influence of work communication, work motivation, and work discipline on employee performance at PT. Atreo Amnyntas Mubarak Batam. The study's background emphasises the importance of enhancing employee performance as a critical factor in organisational performance, particularly in addressing the challenges posed by competitive dynamics and evolving work environments. This research employs a quantitative methodology utilising a survey instrument targeting employees as respondents. Data were collected through questionnaires that had been tested for validity and reliability, and then analysed using multiple linear regression. The study's results indicate that partial work communication, work motivation, and work discipline have significant effects on employee performance. In addition, the results of simultaneous tests prove that work communication, work motivation, and work discipline together have a substantial effect on employee performance at PT. Atreo Amnyntas Mubarak Batam. These findings indicate that improving employee performance can be achieved through effective work communication management, continuous motivation, and consistent work discipline. At the same time, this study is anticipated to make theoretical contributions to the development of human resource management research and to make practical contributions to the company's management in formulating policies to improve employee performance.